2010
DOI: 10.1002/jbm.a.32679
|View full text |Cite
|
Sign up to set email alerts
|

New predictive model for monitoring bone remodeling

Abstract: The aim of this article was to present a new thermodynamic-based model for bone remodeling which is able to predict the functional adaptation of bone in response to changes in both mechanical and biochemical environments. The model was based on chemical kinetics and irreversible thermodynamic principles, in which bone is considered as a self-organizing system that exchanges matter, energy and entropy with its surroundings. The governing equations of the mathematical model have been numerically solved using Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 78 publications
(193 reference statements)
0
56
0
Order By: Relevance
“…In the last decades, several research groups have worked in the development of new models, to describe the bone remodelling process, taking into account different stimuli in bone cell regulation, like mechanical strain, microdamage, cell biology, metabolic factors and other external contributions [8,10] . From a biochemical point of view, the first model correlated the differential activity of parathyroid hormone (PTH) as a regulator for bone resorption and formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, several research groups have worked in the development of new models, to describe the bone remodelling process, taking into account different stimuli in bone cell regulation, like mechanical strain, microdamage, cell biology, metabolic factors and other external contributions [8,10] . From a biochemical point of view, the first model correlated the differential activity of parathyroid hormone (PTH) as a regulator for bone resorption and formation.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it was the time to demonstrate the role of hormones like autocrine and paracrine in the regulation of bone remodelling. Finally, a signalling pathway known as RANK/RANKL/OPG to regulate bone cells activities [10] . It was also found that this signalling pathway RANK-RANKL-OPG is an important regulation of the paracrine interactions between osteoblasts and osteoclast [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the stimulus which initiates bone remodeling is formulated as proportional to the damage energy dissipation summed over all daily loading cycles. Although these models have been to some extent successful in predicting normal bone architecture, they suffer from some major drawbacks: These models use only mechanical signals to stimulate bone remodeling and fail to consider the underlying biological mechanisms that control the bone remodeling process [4,31].…”
Section: Introductionmentioning
confidence: 99%
“…If strain level is below a set point, bone is resorbed, and if it exceeds this set point, new bone is formed. The mechanostat theory is a qualitative theory because the set-point is not specified [31]. Nevertheless, several mechanobiological models have been presented so far [25,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation